PERAN BUDAYA LOKAL TERHADAP PENCEGAHAN ILLEGAL FISHING - Randi; Kamaruddin; Gamlan Dagani (Halu Oleo University, 2024)
This study aims to determine the Role of Local Culture in Preventing Illegal Fishing. The research method combines normative and empirical approaches to determine the role of local culture in preventing illegal fishing in coastal communities in Southeast Sulawesi. The results of the study indicate that the role of local culture in Southeast Sulawesi, especially local wisdom and social sanctions, has an important contribution to preventing illegal fishing in coastal communities. The synergy between strong customary traditions and formal government policies is the key to success in maintaining the sustainability of marine ecosystems. These efforts can be strengthened through the development of local wisdom-based education, increasing the capacity of customary leaders, formulating responsive policies that involve the community, and strengthening community-based monitoring systems. With this holistic approach, the sustainability of marine resources can be realized, while preserving the traditional values ​​that are the identity of the local community.